"We are in this together": Experiences of relationship satisfaction in couples raising a child with autism spectrum disorder. (February 2019) - Sim, Angela; Cordier, Reinie; Vaz, Sharmila; Falkmer, Torbjörn
Highlights: Many couples adapt positively to raising a child with ASD and report relationship satisfaction. A strong partnership is beneficial to maintaining relationship satisfaction. Shared beliefs, teamwork and shared experiences contribute to a strong partnership. Health professionals can support couples to strengthen their partnership and relationship satisfaction. Relationship satisfaction can promote positive family adjustment to raising a child with ASD. Abstract: Background: Couple relationships play an integral role in family adjustment when a child has autism spectrum disorder (ASD), yet, it is unclear what factors contribute to the maintenance of relationship satisfaction in these couples. Method: Using phenomenology, data from eleven couple interviews were analysed to gain an understanding of the lived experiences of relationship satisfaction when raising a child with ASD. Results: The overall essence of "We are in this together" reflected the attitude that a strong partnership was beneficial in maintaining relationship satisfaction. This essence was captured in three main themes: 1) Shared beliefs, 2) Teamwork and 3) Shared experiences which closely paralleled the Walsh family resilience framework. Conclusions: Couples can be supported in these key areas to strengthen their relationship to serve as a source of resilience for families with a child with ASD.